FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMILIHAN KARIR SEBAGAI AKUNTAN PUBLIK DAN NON AKUNTAN PUBLIK (Studi Kasus pada Mahasiswa Progran Studi S1 Jurusan Akuntansi Universitas Mercu Buana Yogyakarta) - Eviy Rosmalinda; Diana Airawaty (Multiplier: Jurnal Magister Manajemen, 2018)
The purpose of this study is to investigate and analyse the factor that will influence the selection of accounting student in a public accounting career and non a public accounting career. Factor that’s influence the career choice become public accounting variabels financial rewards, professional training, social value, work environment, labor market considerations and personality. The primary data in this study were obtained by performing the university Mercu Buana Yogyakarta Campus 2 accounting student discourse with a total sample of 69 students. Analysis tools used in this study in logistic regression. The resuld showed that simultaneous variable financial rewards, professional training, social value and personality significantly influence career choice public accountants. While work environment and labor market consideration not significan influence career choice public accountants. Keywords: Financial reward; professional training; social value, work environment; labor market considerations